Misconceptions or mental models. Issue 1 (May 2021) - Sands, David
Abstract: This paper presents a detailed study of inconsistent thinking by entry-level students on a troublesome question on the Force Concept Inventory. Two cohorts of students separated by three years were asked a series of questions after completing the Force Concept Inventory. The questions were aimed at eliciting their background knowledge of Newton's laws of motion along with their approach to question 26. For example, were they guessing, eliminating some impossibilities, reasoning the answer, etc. There was no common or even predominant approach and considerable evidence of inconsistent thinking. The results are discussed in the light of recent literature on the nature of thinking and in particular the debate over logical reasoning versus reasoning by mental models. It is argued that the mental-models perspective explains many aspects of the data and moreover is more conducive to teaching approaches than the misconceptions perspective.